Answer:
x = 2
Explanation:
First translate the image into an equation using the key. Once you do that, your equation should look like this:
(x + x + x) + (-1 + -1 + -1 + -1 + -1) = (-x + -x) + (1 + 1 + 1 + 1 + 1)
________________________________
3x - 5 = -2x + 5
(given)
________________________________
3x - 5 = -2x + 5
+5. +5
(addition property of equality)
*cancel out -5 on the left hand side, and isolate it from x by adding +5 on each side*
__________________________
3x = -2x + 10
+2x +2x
(addition property of equality)
*cancel out the negative 2x, and isolate it from the constant term on the right hand side by adding 2x on both sides*
________________________________
5x = 10
÷5. ÷5
(division property of equality)
*divide by 5(GCF) on both sides to isolate
x by itself*
________________________________
x = 2
________________________________
If you want to test this solution, substitute this back into the equation.
x = 2 → 3x - 5 = -2x + 5. 3(2) - 5 = -2(2) + 5 = 6 - 5 = -4 + 5 = 1 = 1